Patient safety climate from the nursing perspective - Vanessa Leal Lira; Sônia Maria de Araújo Campelo; Nayra Ferreira Lima Castelo Branco; Herica Emilia Félix de Carvalho; Denise de Andrade; Adriano Menis Ferreira; Ivonizete Pires Ribeiro
ABSTRACT Objective: To analyze the patient safety climate in intensive care units from the nursing perspective. Methods: Cross-sectional study developed with 87 nursing professionals working in three Intensive Care Units of a public hospital for emergency services in Piauí from October to November 2018. The study used a validated Safety Attitudes Questionnaire (SAQ). In the inferential analysis, the Student's t-test, Mann-Whitney, and Kruskal-Wallis were performed. Results: The total SAQ score obtained a mean of 68.57. In analyzing the scores obtained for each domain in the general SAQ, the Job Satisfaction, and Teamwork Climate domains were those that obtained the highest scores, and the lowest score was for the Perception of Hospital Management domain. Conclusion: The safety attitudes assessed from the perspective of the nursing team proved to be unfavorable.